Intermittent fasting activates macrophage migration inhibitory factor and alleviates high-fat diet-induced nonalcoholic fatty liver disease - Li, Dezhao; Dun, Yaoshan; Qi, Dake; Ripley-Gonzalez, Jeffrey W.; Dong, Jie; Zhou, Nanjiang; Qiu, Ling; Zhang, Jie; Zeng, Tanghao; You, Baiyang; Liu, Suixin (Scientific reports, 2023)
Switching to normal diet (ND) is the regular therapy for high-fat diet (HFD)-induced nonalcoholic fatty liver disease (NAFLD). Intermittent fasting (IF) is a unique treatment which may exhibits better therapeutic efficacy. Thus, we aim to investigate the therapeutic effects of these treatments and exploring the mechanisms. In the present study, NAFLD mouse model was induced by a 10-week HFD. Thereafter, mice adopted continued HFD, ND, or IF for the next 12 weeks. Finally, the liver was then harvested to assess lipid deposition, lipid metabolism, apoptosis, and autophagy, while blood was collected to determine blood glucose and insulin. The results showed that IF and ND treatment improved lipid deposition and metabolic disorder of NAFLD mice; the increasing body weight, liver weight, and HOMA-IR index of HFD mice were also alleviated by IF and ND. Furthermore, IF and ND treatment activated the macrophage migration inhibitory factor (MIF)/AMPK pathway and regulated its downstream autophagy and apoptosis. However, the efficacy of IF was better than ND. Both IF and ND activates MIF signaling and alleviate the lipotoxicity of NAFLD while IF therapy is more effective than ND. The different MIF up-regulation might be the underlying mechanism of why IF benefits more than ND.